IMPLICATIONS OF PERMA NUMBER 7 OF 2022 CONCERNING. ADMINISTRATION OF CASES AND TRIALS. JUDGMENT AS WELL. ELECTRONICS AGAINST. PRINCIPLES OF CIVIL PROCEDURE LAW: IMPLIKASI PERMA NOMOR 7 TAHUN 2022 TENTANG. ADMINISTRASI PERKARA DAN PERSIDANGAN. PENGADILAN SECARA. ELEKTRONIK TERHADAP. ASAS-ASAS HUKUM ACARA PERDATA - Yogo Risnandri; Hufron (SOSIOEDUKASI, 2024)
Background: There is a growing need for courts to implement electronic-based administration, or E-Court, as technology advances. Objective: To understand, study and analyze whether PERMA Number 7 of 2022 regarding Electronic Administration and Trial of Cases in Court complies with Indonesian civil procedural law principles. Method: Qualitative research with a normative legal perspective demonstrates that e-court use can typically increase judicial efficiency. Result: Some applications are still opposite from the principles of civil procedural law, HIR and RBG. This condition can be seen in the implementation of the principle of open hearings to the public in the court, the application of the Nemo Judex Idoneus in Propria Causa principle, and SEMA 1 of 2023 concerning Surat Tercatat (Registered Letters), which violate the provisions in the HIR and RBG. Conclusion: This situation makes sense because it will take time to create new civil procedural laws and there is an urgent need to improve the court's efficacy and efficiency.